Two interacting electrons in N-dimensional quantum dot with generalized cornell potential - DOSSA, Finagnon A.; DAGOUDO, Léonie; AVOSSEVOU, GABRIEL YVES HUGUES (My University, 2023)
In this work, the interacting electrons in N-dimensional quantum dot with generalized Cornell potential in the presence of an external magnetic eld are investigated using the Laplace transformation method. The energy eigenvalues and the corresponding normalized wave functions are calculated. The parameter dening the force of a constant traction on the electrons is quantied and represents well the negative of the electric force. The spectrum for some special cases of the generalized Cornell potential is obtained. One of the applications of such models is the calculation of heavy quarkonia mass spectra. We have calculated these masses and the current results are in agreement with the experimental data.
Keywords: quantum dot; Cornell potential; Laplace transformation; heavy quarkonium